Two-dimensional molybdenum disulfide as adsorbent for high-efficient Pb(II) removal from water. (December 2017) - Liu, Chang; Jia, Feifei; Wang, Qingmiao; Yang, Bingqiao; Song, Shaoxian
Graphical abstract: Highlights: 2D molybdenum disulfide exhibited superb adsorption capacity of Pb 2+ . Complexation between Pb 2+ and intrinsic S or O atoms exposed on 2D molybdenum disulfide surface was proposed. 2D molybdenum disulfide might be an excellent Pb 2+ adsorbent in wastewater treatment. Abstract: Two-dimensional (2D) molybdenum disulfide might be highly capable of lead removal from wastewater due to the huge sulfur-rich surface area. An attempt was made to explore the feasibility of using 2D molybdenum disulfide as a super adsorbent in water in this work. Adsorption isotherm and kinetics and SEM-EDS were conducted to investigate Pb(II) adsorption capacity at the interface of 2D molybdenum disulfide/water, and XPS was used to study the adsorption mechanism. The results indicated that 2D molybdenum disulfide had a dramatic efficiency for Pb(II) removal from water with a 1479 mg/g adsorption capacity. The adsorption followed the Freundlich isotherm model and fitted well with both the pseudo-first-order and pseudo-second-order kinetics models. The adsorption might be attributed to the chemical adsorption due to the complexation of Pb(II) with intrinsic S or O atoms exposed on 2D molybdenum disulfide surfaces, together with electrostatic adsorption.